Assessment of Metallic Contaminants in Grinded Millet using Domestic Grinding Machine - J. K. Odusote; G. A. Soliu; I. I. Ahmed; S. Abdulkareem; K. A. Akande (Nigerian Journal of Technological Development, 2017)
In this study, the quantity of metallic contaminants extracted from grinded millet was evaluated. The millet was grinded in three different forms; wet, paste, and dry forms for up to 3 minutes using locally fabricated grinding machine with cast grinding discs. Separate grinding discs were used for different millet forms, while the same quantity of millet, 1 kg, was used throughout the experiments. The millet was soaked for 24 hours before grinding in order to obtain wet and paste forms of the millet. Metallic contaminants were carefully extracted from the grinded millet using magnetic bed along with sedimentation and decantation. The extracted materials were then quantified to ascertain the food form that produces the highest amount of metallic contaminants. Also, the wear rate of the grinding disc was also determined with respect to the grinding time. The results show that the wet form has the highest amount of metallic contaminants of about 1.397 g followed by the paste form with 1.075 g. The dry form has the least value corresponding to 0.945 g. The grain sizes of the metallic contaminants were calculated to be 12.095 nm for the wet form, 8.056 nm for paste form while the dry form has the smallest grain size of 3.124 nm. The results revealed that metallic contaminants are always contained in grinded food processed with local grinding discs. Thus, materials with better wear resistance should be selected for production of grinding discs to be used for food processing.